Perfectionism in the Transactional Stress Model - Zureck, Elisabeth; Altstötter-Gleich, Christine; Gerstenberg, Friederike X.R.; Schmitt, Manfred (Personality and individual differences, 2015)
•We implemented a social stress test and a placebo condition.•We assessed perfectionism (PS, PC), appraisals and affective stress response.•PS predicted cognitive appraisals but not the affective stress response.•PC predicted the affective stress response mediated by cognitive appraisals.•An interaction of PS, PC and condition predicted affective stress response. Applying an experimental between-subject design with varying situational demands (N=168) we investigated the main and interactive effects of perfectionistic strivings (PS) and perfectionistic concerns (PC) on primary threat appraisal and secondary self-confidence appraisal and if these appraisals mediate the effects of PS and PC on the affective stress-response to a given situation. Path analyses revealed differential effects of experimental condition, PS and PC on the cognitive appraisals and the affective stress response. While the positive effects of PS on cognitive appraisals did not extend to the affective stress response directly or indirectly, the negative effect of PC on the affective stress response was fully mediated by the secondary self-confidence appraisal. Additionally we found a significant three-way interaction of PS, PC and experimental condition predicting the affective stress response that was not mediated by the cognitive appraisals.